PERAN ORANG TUA DALAM MEMBANGKITKAN SEMANGAT BELAJAR ANAK USIA SEKOLAH DASAR PASCA PENDEMI COVID 19 DI KOTA PADANG - Revi Handayani; Risma Wiwita; Riska Mayeni; Ramadhani Ramadhani (STKIP Pesisir Selatan, 2022)
This research describes the post-covid-19 situation and the readiness of elementary school children to carry out face-to-face learning again. The qualitative descriptive research method of this research is used to analyze events, phenomena, or conditions of social reality. Data were obtained from various sources, data collection techniques through instruments carried out by researchers, such as observation, interviews and documentation. The research subjects are informants, namely people who provide an overview of the current situation, namely a social situation or social situation consisting of three elements, namely places, actors, and activities that integrate synergistically. Then the analysis and conclusions, the location of this research is in the city of Padang. This research sees that in re-implementing post-online learning during Covid 19, the role of parents must be fully carried out to revive children's enthusiasm because they are used to learning using technology such as gadgets. Currently, the city of Padang has conducted full face-to-face meetings, asking elementary school-age students to attend. This is certainly not easy to change because it has long been complacent because at this age children need the active role of parents as guides in getting to know learning again. The results of this study post-covid 19 learning can be carried out well if there is full guidance for children, and the readiness of the parents is very meaningful